A homozygous PMS2 founder mutation with an attenuated constitutional mismatch repair deficiency phenotype. Issue 5 (17th February 2015) - Li, Lili; Hamel, Nancy; Baker, Kristi; McGuffin, Michael J; Couillard, Martin; Gologan, Adrian; Marcus, Victoria A; Chodirker, Bernard; Chudley, Albert; Stefanovici, Camelia; Durandy, Anne; Hegele, Robert A; et al.
Abstract : Background: Inherited mutations in DNA mismatch repair genes predispose to different cancer syndromes depending on whether they are mono-allelic or bi-allelic. This supports a causal relationship between expression level in the germline and phenotype variation. As a model to study this relationship, our study aimed to define the pathogenic characteristics of a recurrent homozygous coding variant in PMS2 displaying an attenuated phenotype identified by clinical genetic testing in seven Inuit families from Northern Quebec. Methods: Pathogenic characteristics of the PMS2 mutation NM_000535.5:c.2002A>G were studied using genotype–phenotype correlation, single-molecule expression detection and single genome microsatellite instability analysis. Results: This PMS2 mutation generates a de novo splice site that competes with the authentic site. In homozygotes, expression of the full-length protein is reduced to a level barely detectable by conventional diagnostics. Median age at primary cancer diagnosis is 22 years among 13 NM_000535.5:c.2002A>G homozygotes, versus 8 years in individuals carrying bi-allelic truncating mutations. Residual expression of full-length PMS2 transcript was detected in normal tissues from homozygotes with cancers in their 20s. Conclusions: Our genotype–phenotype study of c.2002A>G illustrates that an extremely low level of PMS2 expression likely delays cancer onset, a feature that could be exploited in cancer preventive intervention.